Implementasi Branding Serta Sosial Media Marketing Melalui Instagram Pada UMKM Pawon Wenak Kelurahan Medokan Ayu Surabaya - Farradiba Jumhury Maharani; Dhani Ichsanuddin Nur (Jurnal Informasi Pengabdian Masyarakat, 2023)
Difficulties in building and developing a business are one of the reasons UMKM’s in Indonesia cannot develop properly. In fact, many UMKM’s choose to close their businesses because there is no development and even experience losses. The cause of the non-development of UMKM’s is the branding factor that has not been applied to their business. In fact, branding is something that is quite important so that a business or business can run and progress. Apart from not implementing branding, another factor that causes UMKM’s to not develop is the lack of optimization in the use of social media as a marketing tool. If business actors cannot keep up with the times, there will be an adverse impact on their business. With direct assistance to UMKM’s, later UMKM actors can apply branding and utilize social media as a means of marketing in selling products from UMKM’s.